Peran Teknologi dan Modal Manusia dalam Meningkatkan Pertumbuhan Ekonomi: Studi pada negara-negara ASEAN dengan pendekatan neoklasik dan pendekatan new growth - Rakhmat Haryono; Heri Lanadimulya; M Hafidz Farhan (Universitas Pasundan, 2021)
Increasing inclusive and quality economic growth can be achieved through increasing capital accumulation through investment as a source of economic growth. But apart from increasing capital accumulation, inclusive economic growth is likely to be greatly supported by increased accumulation of human capital and the use of technological factors. This study tries to measure the role of technology and human capital on economic growth with the neoclassical approach and the new growth approach. The method used is by using panel data from 10 ASEAN countries from 1971-2017. The main variables in this study are human capital and technology, while the control variables are population growth, capital growth, and depreciation. The results of the study found that both in the neo-classical approach and in the new growth approach, all variables have a significant influence, while in terms of the feasibility of the new growth approach model is better than the classical approach, which is indicated by the coefficient of determination in the new growth approach which is 87% greater than the coefficient of determination neo-classical approach is 21%.